Die Entstehung des Gleichnisses vom reichen Kornbauern (Lk 12,13-21) - Neumann, Nils 1975- (2018)
The Lukan parable of the Rich Fool (Lk 12,13-21) substantially bears the signature of the third gospel's author. Luke takes fundamental motifs from Jesus' speech about worrying, which is available to him in written form (Lk 12,22-34; cf. Mt 6,19-33). The parable's narrative structure on the other hand stems from the Menippean branch of Cynic Philosophy, where several variations of it are documented. By combining these elements the writer compiles a new parable, also adding characteristic features of his own narrative style. Thus, the paragraph Lk 12,13-21 is clearly an example of its author's literary creativity.
Keywords: Composition; Gospel of Luke; Menippean Literature; Parable of the Rich Fool; Sources